EFFECT OF FE-FORTIFIED TEMPE ON HEMATOLOGIC STATUS IN PREGNANT MOTHERS WITH ANEMIA - Anggraini Wulandhari; Supriyana Supriyana; Bahiyatun Bahiyatun; Soeharyo Hadisaputro; Imam Djamaluddin Mashoedi (Belitung Nursing Journal, 2017)
Background: The prevalence of anemia among pregnant mothers is still high in Indonesia. Fe-fortified tempe is a traditional soy product originating from Indonesia considered able to increase hematologic status. Objective: This study aims to determine the effect of Fe-fortified tempe on hemoglobin, hematocrit, and erythrocyte levels in pregnant women with anemia. Methods: This was a true-experimental study with randomized pretest and posttest control group design, conducted on November - December 2016 in Bandarharjo Health Center, Semarang, Indonesia. Sixty-eight respondents were selected using simple random sampling, with 34 respondents were randomly assigned to each group. Blood examination was performed in each respondent. Mean, percentage, and frequency distribution of respondents were described. Paired t test and independent t test with α = 0.05 were performed to analyze the data. Result: Findings showed that hemoglobin, hematocrit, and erythrocyte levels before and after intervention in the treatment group showed p-value 0.000 (< 0.05), which means there was a significant effect of Fe-fortified on the increase of hemoglobin, hematocrit, and erythrocyte levels. Conclusion: There was an increase in hemoglobin, hematocrit, and erythrocyte levels after given Fe-fortified tempe for 10 consecutive days. It is suggested that pregnant women can consume Fe-fortified tempe.